2015
DOI: 10.3233/jad-141314
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in the Apolipoprotein-A1 Gene is Associated with Episodic Memory Performance in Healthy Older Individuals

Abstract: Findings demonstrated that epigenetic control of APOA1 expression and DNA methylation levels are associated with episodic memory performance in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…The Apo A-1 proteoforms b and d were increased in serum and decreased in CSF, whereas Apo A-1 proteoform c increased both in CSF and serum. Our results can be related to a recent study on the methylation of the promoter region of the APOA1 gene [19]. This epigenetic modification promotes the switch-off of the gene even though not associated with a protein decrement in serum.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The Apo A-1 proteoforms b and d were increased in serum and decreased in CSF, whereas Apo A-1 proteoform c increased both in CSF and serum. Our results can be related to a recent study on the methylation of the promoter region of the APOA1 gene [19]. This epigenetic modification promotes the switch-off of the gene even though not associated with a protein decrement in serum.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, a negative association with memory performance has been related to increased DNA methylation and higher serum levels of Apo A-1 [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cohorts, the platform was the same, methylation was measured in cord blood, exposure was categorized in a similar way (any smoking by the mother during pregnancy), Caucasian/European ancestry participants were included in the analyses (subset of NEST), and the statistical model and covariates were aligned. This approach also has been used in several studies that first identified CpG sites using arrays, and then validated the loci using PSQ (Breton et al 2009; Devaney et al 2015; Lazarus et al 2015). …”
Section: Approaches For Validating/replicating Loci That Emerge As Tomentioning
confidence: 99%
“…Since SR-BI has already been identified as a major receptor for HDL (with their major apolipoprotein [apo] A-I ) as well as for the earlier-described LCM/ND nanoemulsion, this multitasking lipid nanoemulsion can arguably serve as a targeted, apo A-I-based, (SR-BI mediated) therapeutic agent for Alzheimer's disease Hottman et al 2014;Robert et al 2016Robert et al , 2017cf. Choi et al 2016;Kitamura et al 2017;Lazarus et al 2015;Ma et al 2015;Slot et al 2017;Velagapudi et al 2017;Yin et al 2014).…”
Section: Targeting Senile Endothelium Brain Biometal (Fe Ca) Dyshommentioning
confidence: 99%